Charge Transfer Chromophores Derived from 3d-Row Transition Metal Complexes - Kira I. Pashanova; Irina V. Ershova; Olesya Yu. Trofimova; Roman V. Rumyantsev; Georgy K. Fukin; Artem S. Bogomyakov; Maxim V. Arsenyev; Alexandr V. Piskunov (Molecules, 2022)
A series of new charge transfer (CT) chromophores of “α-diimine-MII-catecholate” type (where M is 3d-row transition metals—Cu, Ni, Co) were derived from 4,4′-di-tert-butyl-2,2′-bipyridyl and 3,6-di-tert-butyl-o-benzoquinone (3,6-DTBQ) in accordance with three modified synthetic approaches, which provide high yields of products. A square-planar molecular structure is inherent for monomeric [CuII(3,6-Cat)(bipytBu)]∙THF (1) and NiII(3,6-Cat)(bipytBu) (2) chromophores, while dimeric complex [CoII(3,6-Cat)(bipytBu)]2∙toluene (3) units two substantially distorted heteroleptic D-MII-A (where D, M, A are donor, metal and acceptor, respectively) parts through a donation of oxygen atoms from catecholate dianions. Chromophores 1–3 undergo an effective photoinduced intramolecular charge transfer (λ = 500–715 nm, extinction coefficient up to 104 M−1·cm−1) with a concomitant generation of a less polar excited species, the energy of which is a finely sensitive towards solvent polarity, ensuring a pronounced negative solvatochromic effect. Special attention was paid to energetic characteristics for CT and interacting HOMO/LUMO orbitals that were explored by a synergy of UV-vis-NIR spectroscopy, cyclic voltammetry, and DFT study. The current work sheds light on the dependence of CT peculiarities on the nature of metal centers from various groups of the periodic law. Moreover, the “α-diimine-MII-catecholate” CT chromophores on the base of “late” transition elements with differences in d-level’s electronic structure were compared for the first time.